Sapropterin for phenylketonuria: A Japanese post‐marketing surveillance study. Issue 1 (24th January 2022) - Tamura, Mina; Seki, Shizuka; Kakurai, Yasuyuki; Chikada, Shuichi; Wada, Kento
Abstract: Background: The aim of this study was to assess the long‐term safety and efficacy of sapropterin in a real‐world setting in Japanese patients with tetrahydrobiopterin (BH4)‐responsive phenylketonuria. Methods: This post‐marketing surveillance study enrolled all of the patients in Japan with confirmed BH4‐responsive PKU who were administrated sapropterin between July 2008 and October 2017. Patients were observed at least every 3 months during follow up, with key data collected on treatment exposure/duration, effectiveness according to physician's judgement, serum phenylalanine levels, and adverse events. Results: Of 87 enrolled patients, 85 patients (male, 42.4%; outpatients, 96.5%) were included in the safety and efficacy analysis sets. Treatment started at age <4 years in 43 (50.6%) patients and the most common starting daily dose was 5–10 mg/kg ( n = 41, 48.2%) with the overall duration of treatment between 0.2 and 17.2 years. Serum phenylalanine levels, according to loading tests, reduced from a baseline level of 9.66 mg/dL (range 0.48–36.80 mg/dL) by >30% in 84 patients. Treatment was deemed effective in 79 of 85 patients (92.9%, 95% confidence interval: 85.3–97.4). One patient (1.2%) experienced an adverse drug reaction (alanine aminotransferase increased) 50 days after the start of administration, which resolved without complications with continued treatment. Conclusions: Sapropterin appears well tolerated and highly effective in Japanese patients treated in a real‐world setting, including those who start treatment at age <4 years and pregnant women.